Dosimetry for 177Lu-DKFZ-PSMA-617: a new radiopharmaceutical for the treatment of metastatic prostate cancer - Delker, Andreas; Fendler, Wolfgang Peter; Kratochwil, Clemens; Brunegraf, Anika; Gosewisch, Astrid; Gildehaus, Franz Josef; Tritschler, Stefan; Stief, Christian Georg; Kopka, Klaus; Haberkorn, Uwe; Bartenstein, Peter; Böning, Guido (European journal of nuclear medicine and molecular imaging, 2016)
Dosimetry is critical to achieve the optimal therapeutic effect of radioligand therapy (RLT) with limited side effects. Our aim was to perform image-based absorbed dose calculation for the new PSMA ligand 177Lu-DKFZ-PSMA-617 in support of its use for the treatment of metastatic prostate cancer.